A documentary history of religion in America ; v. 2 - Gaustad, Edwin Scott (Grand Rapids, MI Eerdmans, 1983)
Contents : v. 2 : Since 1865 Includes bibliographical references and index.
Keywords: United States -- Religion -- History -- Sources